COMPARISON OF POSTOPERATIVE OUTCOMES WITH AND WITHOUT TRICUSPID LEAFLET DETACHMENT IN PATIENTS UNDERGOING VENTRICULAR SEPTAL DEFECT REPAIRS - Riaz, Muhammad Usman; Waqar, Tariq; Ahmad Raza Baig, Mirza (Journal of Postgraduate Medical Institute, 2017)
Objective: To compare outcomes of peri-membranous ventricular septal defects (VSD) closure with and without tricuspid valve detachment (TVD) in terms of residual VSD's, postoperative heart blocks, tricuspid regurgitation and operative time. Methodology: This retrospective study was conducted in Department of Pediatric Cardiac Surgery, Chaudhry Pervaiz Elahi Institute of Cardiology, Multan from January 2009 to June 2015. There were 32 patients in tricuspid detachment (TVD) group and 204 in non-TVD group. The study endpoints were any incidence of postoperative residual VSD, heart block or tricuspid regurgitation. Fischer's exact test was used to compare study endpoints. Results: In TVD group 18 (56.3%) were male and in non-TVD group 141 (68.1%) were male. Mean age in the TVD group was 13.38 ±6.91 years. While in non- TVD group it was 11.34 ±6.06 years. Mean cross clamp time was 67.91 ±27.3 minutes and mean bypass time was 98.13 ±32.5 minutes in TVD group. In non- TVD group mean cross clamp time was 58.63 ±24.46 minutes and bypass time was 93.40 ±30.11 minutes (p values were 0.07 and 0.44 respectively). Only 1 (3.1%) case was noted in TVD group with moderate tricuspid regurgitation and 4 (2.0%) cases were noted in non-TVD group. One (3.1%) case was noted with residual VSD in TVD group while 7 (3.4%) were noted in non-TVD group. Conclusion: In our study difference in outcomes did not come up to a statically significant difference but it showed low incidence of tricuspid regurgitation and residual VSD in TVD group.